Factors Associated With Common Mental Disorders and the Presence of Noncommunicable Diseases During the COVID-19 Pandemic in Indonesia: A Study in Bogor, West Java - Suryaputri, Indri Yunita; Wurisastuti, Tri; Tjandrarini, Dwi Hapsari; Riyadina, Woro (Journal of Population and Social Studies [JPSS], 2023)
The coronavirus disease (COVID-19) pandemic has significantly impacted the mental health of Indonesians, including those with noncommunicable diseases (NCDs) and those without. However, it is known that COVID-19 has a higher fatality rate in people with NCDs. This study aimed to determine the difference in the prevalence of common mental disorders (CMD) among respondents with and without NCDs and identify the associated factors of CMD from each sub-sample. This cross-sectional study used respondents from the Bogor Cohort Study of noncommunicable disease risk factors. The NCDs in the current study included hypertension, coronary heart disease (CHD), stroke, and diabetes mellitus (DM). The diagnosis of NCD was determined by trained medical professionals following research protocols. A total of 2,936 participants were involved in this study, including 1,734 with NCDs and 1,202 without. Multiple logistic regression was used to analyze factors associated with CMD in respondents with and without NCDs. The prevalence of CMD was slightly higher in respondents with NCDs (5.1%) than in those without NCDs (3.6%). Experiencing COVID-19 symptoms in the last six months was a factor associated with CMD in both groups; those with NCDs (AOR = 4.156; 95% CI [2.37, 7.30]; p < .001) and those without (AOR = 5.797; 95% CI [2.63, 12.78]; p < .001). Not having health insurance was a factor associated with CMD, only in respondents with NCDs (AOR = 2.582; 95% CI [1.35, 4.93]; p = .004). Female gender and low education were factors associated with CMD only in respondents without NCDs. During the COVID-19 pandemic, newly diagnosed subjects with NCDs and non-adherence to treatment were identified as factors associated with CMD in respondents with NCDs who had undergone PCR and/or rapid testing. During the pandemic, the knowledge of COVID-19 symptoms and health insurance ownership significantly impacted the community’s wellbeing, not only for physical but also for psychological health.